Prognostic predictors for ambulation in children with cerebral palsy: a systematic review and meta-analysis of observational studies - Orawan Keeratisiroj (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Purpose: The purpose of this study is to investigate the prognostic predictors for ambulation in children with cerebral palsy using meta-analysis of observational studies. Method: Electronic searches were conducted in PubMed, SCOPUS, CINAHL, ProQuest, Ovid, Wiley InterScience, and ScienceDirect databases from their start dates to December 2015. Results: Of the 1123 identified articles, 12 met the inclusion criteria for qualitative synthesis, eight of which were deemed appropriate for meta-analysis. Qualitative synthesis found that the type of cerebral palsy, early motor milestones, primitive reflexes and postural reactions, absence of visual impairment, absence of intellectual disability, absence of epilepsy or seizure, and ability to feed self were indicated as potential predictors for ambulation. Meta-analysis detected four significant prognostic predictors for ambulation: sitting independently at 2 years, absence of visual impairment, absence of intellectual disability, and absence of epilepsy or seizure. Conclusion: These prognostic predictors should be taken into consideration in therapeutic plans and rehabilitation goals, especially sitting independently before the age of 2 years.Implications for rehabilitation The meta-analysis supports strong evidence that sitting independently at 2 years of age, absence of visual impairment, absence of intellectual disability, and absence of epilepsy or seizure are positive predictors for ambulation in children with cerebral palsy. The therapeutic plans and rehabilitation goals should be considered cautiously for these predictors, especially sitting independently before the age of two years.